1999
DOI: 10.1080/0263514990170104
|View full text |Cite
|
Sign up to set email alerts
|

Transcending Cultural Borders: implications for science teaching

Abstract: The current development towards 'science for all' in all parts of the globe necessitates that consideration be given to how pupils move between their everyday life-world and the world of school science, how pupils deal with cognitive conflicts between those two worlds, and what this means for effective teaching of science. This paper reviews a new cognitive explanation-collateral learning theory-for how pupils cope with disparate worldviews mediated by transcending cultural borders between their everyday cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 55 publications
0
70
0
7
Order By: Relevance
“…First, the framework requires an assumption that learners want to cross borders. Jegede and Aikenhead (1999) support this drawback by recognizing that students who actively resist science learning, such as Fatima in Larson's study (1995), are not included in the border-crossing framework.…”
Section: Cognitive and Social Considerations For Science Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the framework requires an assumption that learners want to cross borders. Jegede and Aikenhead (1999) support this drawback by recognizing that students who actively resist science learning, such as Fatima in Larson's study (1995), are not included in the border-crossing framework.…”
Section: Cognitive and Social Considerations For Science Learningmentioning
confidence: 99%
“…The positive relationship between protective mechanism and collateral learning contributes to meaningful learning. As Jegede and Aikenhead (1999) state: "For many pupils, learning science in order to imbibe its culture meaningfully often involves cognitive conflicts of some kind. Therefore meaningful learning often results in parallel, dependent or secured collateral learning of some kind" (Jegede & Aikenhead, 1999, p. 52).…”
Section: Protective Mechanismsmentioning
confidence: 99%
“…Nevertheless, this potential of HPS to humanise science and to challenge traditional views about scientists and scientific work has been recently questioned (Hodson 1999;Jegede and Aikenhead 1999;Krugly-Smolska 2013;Allchin 2014;Sarukkai 2014), with special attention to which type of HPS is being advocated. The current debates about gender and cultural diversity in science, such as the ones promoted by the US Department of Commerce (see http://www.esa.doc.gov/under-secretary-blog/education-promotes-racial-and-ethnic-equalityscience-technology-engineering) and by the Royal Society in London (see https://royalsociety.…”
Section: Why and Which Hps In Science Education?mentioning
confidence: 99%
“…According to Jegede and Aikenhead (2002), different students' cultural backgrounds became a problem for students to understand western science. In line with this, Suparman (1993) also found that there was a socio-cultural linkage to students' learning.…”
Section: Introductionmentioning
confidence: 99%